The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1101/2021.07.12.21260377
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of BNT162b2 vaccination and isolation on SARS-CoV-2 transmission in Israeli households: an observational study

Abstract: Background Massive vaccination rollouts against SARS-CoV-2 infections have facilitated the easing of control measures in countries like Israel. While several studies have characterized the effectiveness of vaccines against severe forms of COVID-19 or SARS-CoV-2 infection, estimates of their impact on transmissibility remain limited. Here, we evaluated the role of vaccination and isolation on SARS-CoV-2 transmission within Israeli households. Methods From December 2020 to April 2021, confirmed cases were identi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 32 publications
2
34
0
Order By: Relevance
“…Further, Painter et al (2021) reported a key observation: rapid and universal induction of SARS-CoV-2-specific CD4+ T-cells after the first mRNA vaccine dose in naive individuals [106]. This observation is extremely important given the gradual development of antigen-specific CD8+ T-cells also observed by other groups [107,108], which reach maximal levels after the second vaccine dose.…”
Section: The Immunity and Virus Transmission After Vaccinationmentioning
confidence: 94%
See 1 more Smart Citation
“…Further, Painter et al (2021) reported a key observation: rapid and universal induction of SARS-CoV-2-specific CD4+ T-cells after the first mRNA vaccine dose in naive individuals [106]. This observation is extremely important given the gradual development of antigen-specific CD8+ T-cells also observed by other groups [107,108], which reach maximal levels after the second vaccine dose.…”
Section: The Immunity and Virus Transmission After Vaccinationmentioning
confidence: 94%
“…In addition, much evidence has demonstrated that they can considerably reduce the risk of SARS-CoV-2 transmission. Concerning the protective effect, vaccinated individuals who become infected are up to 78% less likely to spread the virus to household members than unvaccinated people [106].…”
Section: The Immunity and Virus Transmission After Vaccinationmentioning
confidence: 99%
“…Early experience in the era of Alpha, when most vaccinated individuals had received their vaccines only in recent months, showed lower viral loads in those with breakthrough infections 42 , and measured viral RNA levels were correlated with low antibody levels around the time of infection 45 . Soon after vaccination and in the era of Alpha, vaccination reduced household transmission to unvaccinated individuals 96 . Evidence on the infectiousness of Delta variant breakthrough cases remains limited.…”
Section: Impact Of Breakthrough Infectionsmentioning
confidence: 99%
“…2 Vaccination also prevents transmission, according to three studies conducted before the onset of the Delta strain. [3][4][5] The BNT162b2 vaccine prevented 80% of infections, and although the decrease in transmission rate in vaccinated people varied from 40% to 80% in these studies, the combined effect resulted in >88% lower risk of SARS-CoV-2 transmission within households.…”
Section: Covid-19 Vaccines Protect Against Emerging Variantsmentioning
confidence: 78%